The Role of Digital Financial Inclusion in Reducing Income Disparities in Underdeveloped Regions - Johny Aninam (Yayasan Inovasi Kemajuan Intelektual, 2022)
This study investigates the transformative role of digital financial inclusion in mitigating income disparities in underdeveloped regions, with a focus on the socio-economic dynamics of 2026. As traditional banking systems often fail to reach remote and marginalized populations due to high operational costs and infrastructure deficits, digital financial services (DFS), ranging from mobile banking to fintech-driven credit, emerge as a critical bridge. Using a quantitative approach with panel data analysis, this research examines how access to digital payment systems, microfinance, and digital insurance influences the Gini coefficient and household income levels in regions with low economic development. The findings suggest that digital financial inclusion significantly reduces income inequality by lowering transaction costs, fostering entrepreneurship, and enhancing financial resilience among the unbanked. The study concludes that while technology acts as a catalyst, its effectiveness is deeply contingent upon digital literacy and supportive regulatory frameworks. This research contributes to the literature on development economics by providing empirical evidence on how the